Visualizing Web Ontologies with CropCircles - Parsia, Bijan; Wang, Taowei; Golbeck, Jennifer (#PROC#ISWC Workshop on End User Semantic Web Interaction 2005, 2005)
We apply a new visualization for complex heirarchies, CropCircles, to the interactive visualization ofWeb Ontologies and E-Connections of Web Ontologies.